The KGB's poison factory from Lenin to Litvinenko - Volodarsky, Boris (Frontline Zenith Press, 2009)
In late November 2006 the world was shaken by the ruthless assassination in London of Alexander Litvinenko, a former Lt Col of the Russian security service (FSB). The murder was the most notorious crime committed by the Russian intelligence on foreign soil in over three decades. The author, Boris Volodarsky, who was consulted by the Metropolitan Police during the investigation and remains in close contact with Litvinenko's widow, is a former Russian military intelligence officer and an international expert in special operations. His narrative reveals that since 1917 - beginning with Lenin and his Cheka - the Russian security services have regularly carried out bespoke poisoning operations all over the world to eliminate the enemies of the Kremlin. The author proves that the Litvinenko's poisoning is just one episode in the chain of murders that continues until the present day. Some of these assassinations or attempted assassinations are already known, others are revealed here for the first time.Uniquely Volodarsky has had a personal involvement in almost every each of the 20 cases, from the radioactive thallium poisoning of the Soviet defector Nikolai Khokhlov in Frankfurt in September 1957 to the ricin 'umbrella murder' of the Bulgarian dissident Georgi Markov in London in 1978.